Character Education Based on Islamic Values - Agus Salim Mansyur; Nanat Fatah Natsir; Aan Hasana; Aja Rowikarim Rowikarim (Syntax Corporation Indonesia, 2021)
This research is based on the background that the condition of some teenagers today tend to be anarchists, criminals, bullying, fights, sex before marriage, forgetting manners, losing manners, arrogant students have become a daily scene. This of course causes problems because these characters are not by the ideals of the Indonesian nation that formal school institutions were established to create a generation with noble character. and the impact of character education based on Islamic values. This research uses a qualitative approach with an analytical descriptive method. The method of collecting data is by using staged but still in-depth interviews and supported by observation and documentation data. Data analysis uses an interactive model, namely by reducing data, displaying data, and drawing conclusions. The results of this study indicate that: in general, instilling character based on Islamic values ??both at SMPN 1 Garut and SMPIT Al-Khoiriyah can form students who believe in one God or monotheism like to worship and have good behavior.This research is based on the background that the condition of some teenagers today tend to be anarchists, criminals, bullying, fights, sex before marriage, forgetting manners, losing manners, arrogant students have become a daily scene. This of course causes problems because these characters are not by the ideals of the Indonesian nation that formal school institutions were established to create a generation with noble character. and the impact of character education based on Islamic values. This research uses a qualitative approach with an analytical descriptive method. The method of collecting data is by using staged but still in-depth interviews and supported by observation and documentation data. Data analysis uses an interactive model, namely by reducing data, displaying data, and drawing conclusions. The results of this study indicate that: in general, instilling character based on Islamic values ??both at SMPN 1 Garut and SMPIT Al-Khoiriyah can form students who believe in one God or monotheism like to worship and have good behavior.